Utilização da urina humana como biofertilizante para produção de alimentos e energia: Caracterização, uso na agricultura e recuperação de nutrientes - Botto, Márcio Pessoa (2013)
This thesis aimed to evaluate the acceptance of eco-sanitation in a peri-urban community in the state of Ceará; to characterize the composition of human urine; to investigate its storage as a treatment method; to develop a parabolic solar concentrator prototype and evaluate the temperatures reached in the region of evaporation of the water contained in the urine; to analyze the performance of castor cultivar BRS Northeastern and corn hybrid in terms of productivity and growth when fertilized with human urine, and assess the impact of this bio-fertilizer in the soil. The results indicates that there were statistically significant differences (p<0.05) between men and women in acceptance of the principles of eco-sanitation. Women were more receptive to ecosan, while men said they would prefer flush toilets. There were differences in nutrient concentrations comparing the samples (male, female, children and the elderly). The storage proved to be a low cost and very effective treatment method considering the temperature of Ceará. The inactivation of 90% of thermotolerant coliform required less than 1 day, and the total inactivation was achieved in 14 days. The tests with the solar concentrator showed that comparing the concentrations of nitrogen and phosphorus in urine before and after the experiment with 22 mm tube, the system promoted an increase of 18% and 13%, respectively, for nitrogen and phosphorus. Concerning urine application in castor, with respect to the thousand seed weight parameter, there was no significant difference. The chemical fertilizer (T1) responded significantly and reached the highest productivity (p <0.05) at the end of the cycle. The average productivity of castor seed were: 1256.7, 1048.5, 671.8, 477.8 and 1081.2 kg ha-1, respectively for T1 (NPKS); T2 (urine + lime); T3 (urine); T4 (0.5 urine) and T5 (1.5 urine). The seed-oil concentrations showed no significant effect (p>0.05). Regarding physical and chemical soil attributes, it was not possible to observe significant differences before and after castor bean plantation. However, the results indicated that the higher the dose of urine applied, the greater the soil electrical conductivity, suggesting a possible salinity from high application rates of urine. Regarding maize, there was no statistical difference (p> 0.05) for diameter and length of the ear comparing chemical fertilizer (T2) and urine (T3, T4 e T5). Otherwise, these treatments generated significant effects (p<0.05) compared to T1, organic fertilizer (manure tanned). The average productivity of husked ears were equal to 5068.8, 7937.5, 8831.3, 7393.8 and 10006.3 kg ha-1, respectively, for T1, T2, T3, T4 and T5, representing a significant effect between urine applied at the rate of 1.5 or 1 and urine at the rate of 0.5 or chemical fertilizer. However, with results already expected, T1 (organic fertilizer) achieved the lowest yield, differing from the other treatments. Thus, the weight of spikes varied according to the type of fertilizer (chemical or urine) and also to the volume of urine applied.